A Case Study of Three Finnish Pre-Service Teachers’ Emotions and Understanding of CLIL During an Online Practicum - Sotiria Pappa (Universidad de La Sabana, 2021)
The novel exigencies of the 2020 COVID-19 pandemic caused a shift towards online learning environments and teleconference platforms, which have also affected teaching practicums. The impact of this approach on teacher preparation is yet unknown and may render pre-service teachers (PSTs) more vulnerable to the challenges of early professional learning through practice, especially when implementing a methodology they have been insufficiently introduced to. Following three students of primary teacher education who opted for a practicum in a CLIL class at a Finnish teacher training school, this case study examines how the online practicum affected these PSTs’ emotions and understanding of CLIL. The case study is based on the analytical categories of teacher identity and emotion and draws on essay, diary, and interview data. The thematic analysis of the data suggests that the online practicum met participants’ expectations for building confidence and was perceived as an overall instructive experience, which was improved by the quality of mentorship and peer support they received. However, feelings of frustration or dissatisfaction accompanied moments of conflict with incoming expectations, principally related to using English in CLIL. The analysis further suggests that the online practicum strengthened participants’ earlier conception of CLIL as a language-oriented teaching tool. Regardless of whether online CLIL practicums remain a future option, acquiring disciplinary and language knowledge alike are important aspects in teacher preparation for CLIL, which could be an optional part of teacher education programs for PSTs who are aware of or sensitive to language as a tool for learning.